2008
DOI: 10.1002/cbf.1528
|View full text |Cite
|
Sign up to set email alerts
|

Protective action of indole‐3‐acetic acid on induced hepatocarcinoma in mice

Abstract: In this study, we report the protective effects of IAA on diethylnitrosamine (DEN)-induced hepatocarcinogenesis. BALB/c mice received daily IAA at 50 (T 50 ), 250 (T 250 ), and 500 (T 500 ) mg Kg À1 per body mass by gavage for 15 days. At day 15, animals were administered DEN and sacrificed 4 h later. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were analyzed in sera. In addition, hepatomorphologic alterations, activity of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…In particular, ROS generated by macrophages stimulated by LPS may cause excessive inflammatory reactions, leading to tissue damage [28]. IAA was previously reported to exhibit free radical elimination effects [29,30]. Consistently, we found that treatment of macrophages with IAA obviously blocked the generation of ROS induced by LPS.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, ROS generated by macrophages stimulated by LPS may cause excessive inflammatory reactions, leading to tissue damage [28]. IAA was previously reported to exhibit free radical elimination effects [29,30]. Consistently, we found that treatment of macrophages with IAA obviously blocked the generation of ROS induced by LPS.…”
Section: Discussionsupporting
confidence: 88%
“…It can be oxidized by the enzyme horseradish peroxidase (HRP) producing cytotoxic compounds, mainly hydroxyl and reactive oxygen species (ROS), able to destroy human cancer cells by membrane and DNA damage . IAA is not easily oxidized by mammalian peroxidases and, therefore, it is well tolerated in humans and even presents positive effects such as an increase in the phagocytic capacity of neutrophils or antioxidant activity . Therefore, the necessity to avoid the premature release of the housed pro‐drug from the silica matrix is not as important as in the case of transporting conventional cytotoxic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In general, IAA is non-toxic to adult mice; however, administration of 500-1000 mg/kg during the mid-gestation period causes microencephaly in the fetus [25]. IAA administration (500 mg/kg) lowers the expression of antioxidant enzymes in the liver and is protective in a model of diethylenitrosoamine-induced hepatocarcinogenesis in mice [26]. The activation of IAA using peroxidase or UV medium wavelength light results in the production of cytotoxic oxidation products that is effective during tumor therapy [27].…”
Section: Discussionmentioning
confidence: 99%